HALAL TOURISM RESEARCH EVALUATION IN 10 YEARS: PAST, PRESENT, AND FUTURE - Sherly Artadita; Hisyam Hisyam (Jurnal Bisnis Manajemen, 2021)
The growing Muslim population worldwide entice many countries to rule the burgeoning halal market, including the tourism sector. With its potential in reshaping the global tourism industry, researchers have been investigating key aspects that may smooth the operations of this unique tourism practice. In line with that, this study aims to analyze the research progress of halal tourism published from 2011 to 2020, summarize the identified key themes and issues, and suggest for future research area in halal tourism. In doing so, qualitative approach combining the bibliometric analysis, network analysis, and content analysis was employed to examine prior research on ‘halal tourism’ obtained from ‘Scopus’ database. VOSviewer and Microsoft Excel software are employed to process a total of 230 peer-reviewed articles, carefully selected based on relevant query and context, such as years, document type, country, journal’s name, authors’ name, number of authors, and the keywords that frequently used by authors. The major finding of this study is the disclosure of keywords connection which grouping into three various clusters. These three clusters have their own prime keyword, namely Islamic tourism, tourism, and halal tourism. The overall analysis and the summary in this study is designed to provide insights that help researchers to design future halal tourism research agenda. As for the practitioners, this article could be a reference that may help them to have better understanding of the development, issues, and possible solutions related to the implementation of halal tourism.